Physico-chemical characterization of some selected soil series of Mymensingh and Jamalpur districts of Bangladesh - Sheel, PR; Chowdhury, MAH; Ali, M; Mahamud, MA (Journal of the Bangladesh Agricultural University, 2016)
The soil physico-chemical properties have been disturbed due to long continued intensive agricultural practices. Under this situation we are approaching rapidly to a very strong future challenge in sustaining the quality of our soil. This study was conducted to evaluate the physico-chemical properties of the selected soil series. The area covered Mymensingh and Jamalpur districts of Bangladesh. Soil samples were collected randomly from different profiles of Lokdeo, Tarakanda, Silmondi and Melandah soil series during March-May, 2014 and analysed. All soils were acidic and textural classes were sandy loam, silt loam, loam, and clay loam. Organic matter and total N contents low to very low. Available S content in the upper layers of most soils were medium to optimum and in the deeper layer low to medium. The exchangeable K, Ca and Na contents were also low. The upper layers of all the locations contained higher amounts of available Zn. The available Cu and Fe contents of most soils were very high. The soils of all locations contained very high amount of available Mn except the deeper layers (45-75 cm) of Melandah which contained optimum amount of available Mn. Soil pH showed negative correlation with total N and available S. Total N showed positive correlation with soil OM, available Cu and available S. There was positive correlation between available S and available Mn. J. Bangladesh Agril. Univ. 13(2): 197-206, December 2015